Torsion of the vermiform appendix in a 16-year-old young man: surgical-radiologic correlation - Habiba Hashimi (Journal of Pediatric Surgery Case Reports, 2021)
Torsion of the vermiform appendix is a rare cause of appendicitis. As it results in ischemia of the appendix, it is usually reported as causing the same symptoms and presentation observed in other cases of appendicitis. Torsion can be primary, in the setting of an otherwise normal appendix, or secondary, when associated with an abnormality such as a mucocele or mass. Despite its rarity, appendiceal torsion has been observed in a wide distribution of age groups, from young children to the elderly. In this report, we describe the case of a 16-year-old young man who presented to an outside facility with several days of pain in the right lower quadrant, and was found to have CT scan findings suspicious for torsion of the appendiceal base. He was transferred to our facility and underwent diagnostic laparoscopy which revealed a 720-degree clockwise torsion of the vermiform appendix about its base, and he was treated with stapled appendectomy. As symptoms from appendiceal torsion will usually be identical to those of more conventional appendicitis, correlation of radiographic findings, when available, with symptoms is useful in identifying torsion as the etiology of the patient's appendicitis and for planning the appropriate operative approach.